Aplicación Web para la Comercialización y Administración de la Asociación Cooperativa de Producción Pesquera y Servicios Múltiples “Bocana Lempa - Jaltepec de R.L”, en el Cantón Las Mesas del Municipio de Tecoluca del Departamento de San Vicente. - García Rodríguez, Juan Saúl; Mejía Durán, Pablo Gumercindo (2024)
El trabajo de graduación describe el desarrollo de una Aplicación web desarrollada para la Asociación cooperativa de producción pesquera y servicios múltiples “Bocana Lempa - Jaltepec de R.L”, en el Cantón las Mesas del municipio de Tecoluca del departamento de San Vicente, con dicha aplicación se automatizaron los procesos de las áreas de comercialización y administración de la cooperativa, los cuales son, Activo fijo, Recursos Humanos, Facturación, Inventario y el desarrollo de una página web a la que accesan los clientes para la realización de pedidos. Con el desarrollo de dicha aplicación se ha obtenido una mayor agilización en los procesos, los cuales conllevan a adquirir mayores logros entre los cuales podemos mencionar: información detallada de los movimientos de inventario, presentación de informes, mejoras en el control de activo fijo, salarios, vacaciones, permisos de los empleados, registro de pedidos realizados desde la página web, impresión de facturas y la reducción del tiempo en el desarrollo de los procesos. SUMMARY The graduation work describes the development of a web application developed for the cooperative association of fish production and multiple services "Bocana Lempa - Jaltepec RL" in the Canton Tables Township Tecoluca the department of San Vicente, with such application they automated processes as the marketing and administration of the cooperative, which are, fixed Assets, Human Resources, Billing, Inventory and development of a website that access to customers for ordering. With the development of this application has gained greater streamlining processes, which lead to acquire greater achievements among which include: detailed information on inventory movements, reporting, improved control of fixed assets, wages holidays, permits employees record orders made from the website, print invoices and time reduction in development processes. Keywords : Online ordering , fixed assets, payroll employees , billing, control fishing. The graduation work describes the development of a web application developed for the cooperative association of fish production and multiple services "Bocana Lempa - Jaltepec RL" in the Canton Tables Township Tecoluca the department of San Vicente, with such application they automated processes as the marketing and administration of the cooperative, which are, fixed Assets, Human Resources, Billing, Inventory and development of a website that access to customers for ordering. With the development of this application has gained greater streamlining processes, which lead to acquire greater achievements among which include: detailed information on inventory movements, reporting, improved control of fixed assets, wages holidays, permits employees record orders made from the website, print invoices and time reduction in development processes.